(3GdfadjI aj eSJMHGJ GdUdGIs - (3GdYGedj GdfHWj GdLRjfi, TeS GdOjf, GdTgjO GdChd, eMeO Hf eci Hf eMeO Hf MGeO, J (B786 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj Ve GdfTQ dLejY GdTJGJ(B... (3hHYO aEfj deG hbaJ Ydi GdMOjKjf GdeTghQjf Yf Cgd Hjf GdfHhI (B... (3hhab Gddg SHMGfg dEedGA GdQSGdI GdCdajI(B...s
(3BNQgG (B:s
(3abO Mci Cf SYjOG Hf YHGOI HGd aj MLQ HGdTGe (B... (3hQejfGg HSgejf ade JNW aDGOgs
(3JHUQI GdeDda (B:s
(3GdTgjO GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B109s
(3GdPQjYI HQbe(B: 1195s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis